PENGARUH LIKUIDITAS, PROFITABILITAS DAN PERTUMBUHAN PENJUALAN TERHADAP PEMBAGIAN DEVIDEN SERTA DAMPAKNYA PADA RETURN SAHAM PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Andini Nurwulandari; Edi Sugiono; Eko Budianto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to examine the effect of the Likuiditas, Profitabilitas and sales growthon the company's stock returns mediated by company dividends. The number of samplesused in this study were 10 samples, all of which were companies that distributeddividends during 2016 – 2020.This research is a research with a quantitative approach. Research data is secondarydata obtained from the financial statements of sample companies listed on the IDX. Theresearch data were then analyzed using the Partial Least Square analysis technique withthe help of the Smartpls program.Based on the results of the analysis in this study, the results obtained that: (1) Likuiditashas a positive effect on company dividends; (2) Profitabilitas has a positive effect oncompany dividends; (3) Sales growth has a positive effect on company dividends; (4)Likuiditas has a positive effect on the company's stock return; (5) Profitabilitas has a positive effect on the company's stock returns; (6) Sales growth has a positive effect onthe company's stock return and (7) The company's dividend has a negative effect on thecompany's stock return.